Regional integration and industry dynamics in the economy of the republic of Angola - Wanderley, Livio Andrade (Geografares, 2016)
The article made an analysis of Angola’s economy to identify sectors and meso on the dynamism and regional integration, respectively. We applied the shift-share model between the years 2003 and 2007 to verify the influences of national growth, productive structure and regional attributes in each sector and meso. There was a national hegemony, especially from two coastal meso, the lack of structural dynamics in meso and sectors and endogenous dynamics in some meso. It was interpreted that the current stage of the Angolan economy is guided by a concentrated dynamism in Luanda and Benguela and the fragile regional integration. Keywords: Sector, Mes, Integration.